The Resurrection of the Dramatic Character: Delgado-García, Cristina. Rethinking Character in Contemporary British Theatre: Aesthetics, Politics, Subjectivity. Berlin/Boston: Walter de Gruyter GmbH, 2015. 224 pages. e-ISBN 978-3- 11-033391-6. - Kurdi, Mária (FOCUS: Papers in English Literary and Cultural Studies, 2018)
For centuries, the character in drama was considered to be the backbone of works for the stage, until the appearance of a wide-scale subversive experimentation with it in postmodern theatre and performance. The writing of Rethinking Character in Contemporary British Theatre was prompted by the recent publication of books and studies that seriously question the presence and dramaturgical role of character in view of the brand-new developments within the genre. Cristina Delgado-García’s point of departure is that the dismissal of dramatic character in this bulk of theoretical literature can be challenged on the grounds that most theorists look at the term “character” in inconsistent ways, their methodology being problematic and their concept of subjectivity too narrow (XI). Surveying the prescriptive considerations about character, Delgado-García posits the hypothesis that by redefining “character” a new, workable approach to investigating certain puzzling character formations in the postmodern British theatre can be achieved (XII). She assumes that “the character cannot be reduced to the impersonating work of the actor” (8) but other aspects of the dramaturgy also contribute to its fictional existence. Contemporary British playwriting, the author continues, exposes “a discontent with ideas of subjectivity formulated around a solid idea” (11). After clarifying its own theoretical positions the study includes the analysis of four British playtexts by major playwrights as well as their performances from the late 1990s to the mid-2000s.Through these analyses, Delgado-García intends to verify “a widening of what character and subjectivity may mean ... [and] begin to undo the hermeneutical stranglehold that liberal-humanism has placed on our examination of theatre’s aesthetic and political engagements with human ontology” (22). Indeed, it is a both intriguing and promising introduction to what follows in the book.